Investigação do impacto do uso de maconha no perfil de sintomas e de resposta ao tratamento de pacientes em primeiro episódio psicótico - Coutinho, Luccas Soares [UNIFESP] (2019)
The present dissertation aims to investigate symptomatic and response-totreatment differences in first-episode psychosis (FEP) patients who use and do not use cannabis. The relationship between FEP and cannabis is complex, with results suggesting that: FEP is anticipated by its use in adolescence; a higher risk for psychosis and a possible influence on symptoms presentation. In the present study, we investigated the influence of cannabis use on symptoms, functionality and remission of antipsychotic naïve FEP patients. A total of 175 subjects were enrolled, of whom 99 were reassessed after 10 weeks of treatment. The variables of this investigation were obtained from the following scales: Positive and Negative Syndrome Scale (PANSS); Addiction Severity Index (ASI 6), Global Assessment of Functioning (GAF) and Clinical Global Impression (CGI). The acute use of cannabis (use in the month prior to the first evaluation) had a significant relationship with higher excitement symptoms and less functionality rates in the first evaluation. Positive, negative, and excitement symptom remission rates were significantly higher in subjects who had used acute cannabis. In the second evaluation, no symptomatic differences were found between the two groups of patients. This effect may be related to discontinuation of acute cannabis use after initiation of treatment, or to an intrinsic characteristic of the response profile of these patients. Therefore, the acute use of cannabis was related to worse symptomatic and functional presentations in FEP patients without prior antipsychotic use.